Potensi Pengaruh Paparan Radiasi Gelombang Elektromagnetik Telepon Genggam Terhadap Kualitas Tidur - Muhammad Al-Fatih; Nurul Octaviani; Reza Muhamad Ilham; Zahra Tiara Pamungkas (Inovasi Kesehatan Global, 2025)
We as humans often skip our cell phones and use them for too long as they are always around us and a part of our lives. Excessive and improper use of cell phones, however, can cause various negative impacts, one of which is a decline in health. Cell phones emit radio frequencies when in use, which produces excessive radiation that can cause many side effects, such as disrupting sleep patterns and sleep quality. This study aims to determine how cell phone radiation affects the human body when falling asleep. This research was conducted using a qualitative method, using a descriptive approach and analyzing previous literature. The results showed that exposure to electromagnetic radiation from cell phones can affect a person's sleep quality, especially for those who use them too often. The level of influence is different for each person, but this radiation is not strong enough to cause serious effects like X-rays because it is not ionized. Nevertheless, it can cause sleep problems and headaches. It is recommended to keep a safe distance from cell phones while sleeping and limit cell phone use before bedtime to reduce the risk.